First aid is associated with improved outcomes in large body surface area burns. Issue 8 (December 2019) - Harish, Varun; Li, Zhe; Maitz, Peter K.M.
Highlights: Treating severe burns (≥20% TBSA) with cool, running water for 20 min up to 3 h is associated with improved outcomes. Benefits are seen in a reduction in TBSA, proportion of the wound that is full thickness, and decreased re-grafting requirements. This study adds to our previous work which demonstrated a significant effect of first aid on outcomes in minor burns. Abstract: Background: Animal studies indicate treating burn injuries with running water (first aid) for 20 min up to 3 h after burn reduces healing time and scarring. We have previously demonstrated the benefits of first aid in minor burn injuries with respect to a reduction in wound depth, faster healing, and decreased skin grafting utilisation. The purpose of this cohort study was to assess the effect of first aid on clinical outcomes in large body surface area burn injuries (≥20%). Methods: Data was prospectively collected for patients with ≥20% TBSA burns from 2004– 2018. Multivariate regression analysis was used to determine the association of adequate first aid with 8 outcomes – mortality, total length of stay, total body surface area (TBSA), percentage/proportion of TBSA that was full thickness [PFTI], TBSA grafted, number of re-grafting sessions, intensive care admission, and intensive care length of stay. Adequate first aid was defined as the application of 20 min of cool, running tap water up to 3 h following the burn injury. Findings: 390 patients were identified. Adequate first aid was received in 35.6% (139) of patients. There was a trend towards a reduction in mortality (OR 0.37; 95% CI 0.12–1.13; P = 0.08). Patients who received adequate first aid had a statistically significant 9.8% reduction in TBSA (95% CI −13.6% to −6.1%; P < 0.0001) as well as a 12% lower PTFI compared to patients who received inadequate first aid (95% CI −19% to −4%; P < 0.01). Whilst there was no significant effect of adequate first aid on the TBSA grafted (P = 0.37), adequate first aid was associated with a significantly less number of re-grafting sessions (95% CI −-0.29 to −0.08; P < 0.001). Interpretation: Adequate first aid with 20 min of running water is associated with improved outcomes in large burn injuries. Significant benefits are seen in a reduction in TBSA, proportion of the burn wound that is full thickness, as well as decreased re-grafting. This has significant patient and health system benefits and adds to the body of evidence supporting 20 min of cooling in burns care.